Política de preservação digital: subsídios a partir da análise diplomática do histórico escolar da UFSM - Pradebon, Daiane Regina Segabinazzi (2016)
The need to set policies that envisage the preservation and access to authentic digital archival documents essential to the memory of the university led to the choice of the theme this research. The objective of this work is to develop of a Digital Preservation Policy of records to the Universidade Federal de Santa Maria (UFSM), using as a reference document the "School Registers" (HE), which is produced by Education Information System (SIE). It is a qualitative research, of exploratory features, conducted through documentary and bibliographic research and direct observation, following the diplomatic analysis model of the InterPARES 3 Project. To meet this goal, first, it developed a diagnosis of the HE in order to assess their status while digital record. Based on this diagnosis, are suggested adjustments for what the HE can be considered a digital records in the field of SIE. The third step is to define the set metadata and requirements for management, preservation and access of the HE. Therefore, it applies by reference to the e-ARQ Brazil Model Requirements for Information Systems Records Management. In the last step, suggest guidelines to ensure the maintenance of Chain of Custody of HE, which support the presumption of authenticity of the records, using as reference the theoretical Hilari Jenkinson, Luciana Duranti and Daniel Flores, as well as regulations of the National Council on Archives. These steps will provide elements for the proposal of a Digital Preservation Policy of records the UFSM and may be used also for other IFES. As a result, it was found, in the light of contemporary diplomatic, that is missing the HE essential requirements for their effective digital preservation. Not there seems to also be a single solution that works as a panacea for the problem since everything in the digital world are vulnerable to technological obsolescence of formats and equipment. This study shows that alternative and solutions should be worked out to ensure the safeguarding of digital records heritage of UFSM, especially those born-digital documents, such as the implementation of a Digital Archival Repository Trusted and the awareness of managers and employees on the importance of establishing policies and regulations on the theme.